2012
DOI: 10.1007/s00253-012-4105-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and production of unsaturated and polyunsaturated fatty acids in yeast: current state and perspectives

Abstract: Recently, many genes involved in the formation of unsaturated and polyunsaturated fatty acids (PUFAs) were isolated. In most cases, their activities were confirmed by expressing them in the well-studied model organism Saccharomyces cerevisiae because its fatty acid compositions are very simple and it does not contain PUFAs. Taking advantage of its genetic tractability and increasing wealth of accessible data, many groups are attempting to produce various useful fatty acids in the model yeasts, mainly in S. cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 112 publications
0
38
0
Order By: Relevance
“…These UFAs are produced from palmitic and stearic acids, respectively, by D9-desaturases and are further converted to PUFAs via D12-desaturases. 27 The accumulation of palmitoleic and oleic acids in OLE2 KO cells argues against the role of OLE2 as an exclusive D9-desaturase and suggests that it may have other enzymatic activities as well. These results are in line with the findings of Krishnamurthy et al, who demonstrated that heterologous expression of CaOLE2 could not reconstitute the phenotype of S. cerevisiae OLE1 (D9-desaturase) mutants, implicating that Ole2 is not a D9-desaturase.…”
Section: Discussionmentioning
confidence: 99%
“…These UFAs are produced from palmitic and stearic acids, respectively, by D9-desaturases and are further converted to PUFAs via D12-desaturases. 27 The accumulation of palmitoleic and oleic acids in OLE2 KO cells argues against the role of OLE2 as an exclusive D9-desaturase and suggests that it may have other enzymatic activities as well. These results are in line with the findings of Krishnamurthy et al, who demonstrated that heterologous expression of CaOLE2 could not reconstitute the phenotype of S. cerevisiae OLE1 (D9-desaturase) mutants, implicating that Ole2 is not a D9-desaturase.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of changes in the initial pH (4)(5)(6)(7)(8) in the medium, as well as temperature (15, 21 and 28°C) were studied on amount of biomass, lipid and PUFA compositions. In ''Temperature Shifting Technique'' first fungi were cultured for 3, 4 or 5 days at 28 °C, after incubation temperature was reduced to 15 °C and the biomass was collected in 7th days.…”
Section: The Selection Of Physicochemical Factors Of Mediummentioning
confidence: 99%
“…However, the price of SCO is rather high than plant and animal oils so that obtaining of oil by microbiological ways are less likely in industrial scales, even in the near future (4,5). In this regard, recent attempts were directed only by biosynthesis of the high value poly unsaturated fatty acids, as food supplements, which plants are not able to produce them (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted on mFADs primarily aims to identify the determinants of desaturase specificity, enabling engineering of mFADs that produce economically or industrially relevant FAs, such as the PUFAs that serve as nutritional supplements or starting materials in the chemical industry [45,46]. Another major research goal is to uncover the mechanistic details of FA desaturation, which might enable rational design of specific inhibitors targeting either the mFADs involved in human metabolic diseases, such as diabetes or obesity [47], or the mFADs essential for pathogenic microorganisms, such as pathogenic yeasts [48][49][50] and trypanosomatids [51,52].…”
Section: Mfadsmentioning
confidence: 99%